2010
DOI: 10.1111/j.1537-2995.2010.02953.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet transfusions from D+ donors to D− patients: a 10‐year follow‐up study of 1014 patients

Abstract: The frequency of anti-D alloimmunization of D- patients after receiving pooled PCs from D+ donors is low. The transfusion of D-incompatible pooled PCs without immunoprophylaxis to D- men or D- women without childbearing potential seems a reasonable and safe alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
70
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 46 publications
8
70
0
Order By: Relevance
“…Since the introduction of mandatory universal pathogen inactivation of all PC in 2011 [2], AP-PC and BC-PC are considered clinically equivalent. However, some differences exist between both types of PC, such as the extent of residual contaminating red blood cells (RBC), which has been shown to be considerably lower for AP-PC (0.00017-0.009 ml) compared to BC-PC (0.036-0.59 ml) [3,4,5,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of mandatory universal pathogen inactivation of all PC in 2011 [2], AP-PC and BC-PC are considered clinically equivalent. However, some differences exist between both types of PC, such as the extent of residual contaminating red blood cells (RBC), which has been shown to be considerably lower for AP-PC (0.00017-0.009 ml) compared to BC-PC (0.036-0.59 ml) [3,4,5,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Some authors reported no incidence of anti-D alloimmunization in this group of patients [84,86,87,90,91,92,93,94,95]; other authors, however, reported an incidence of anti-D alloimmunization that ranged from 2.7 to 18.7% [83,88,89,108]. …”
Section: Part 2: Plt Transfusion and The D Antigenmentioning
confidence: 98%
“…In some of the reports on D alloimmunization after D incompatible PLT transfusion, the percentage of ABO incompatible transfusions is provided; it ranges between 43 and 90% (table 3) [84,87,88,91,93,95]. Thus, the protective effect associated with the transfusion of ABO and D mismatched RBCs is unlikely to be seen in current clinical practice given the high incidence of ABO matched transfusions in the studies reported [99].…”
Section: Part 2: Plt Transfusion and The D Antigenmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-D alloimmunization can therefore occur when platelets from RhD-positive donors are transfused to RhD-negative patients. Various studies of RhD-negative recipients receiving RhD-positive platelet transfusions reported an incidence of 0-19% RhD alloimmunization in cancer patients [5,6,7,8]. Prevention of anti-D alloimmunization by administering Rh immunoglobulin is a well-established practice for RhD-negative pregnant women to prevent hemolytic disease of the newborn (HDN).…”
Section: Introductionmentioning
confidence: 99%